Design and Analysis of a Generalized High-Order Disturbance Observer for PMSMs with a Fuzy-PI Speed Controller - Suleimenov, Kanat; Duc Do, Ton (IEEE Access, 2022)
This paper proposes a generalized high-order observer for estimating total disturbance of permanent magnet synchronous motors (PMSMs). This total disturbance is dominated by load torque but also includes many other terms such as frictions, viscous force, Eddy and flux pulling forces, and noises. Comprehensive experimental results and analyses under various scenarios will be presented to find the appropriate order of the observer. We will compare the performance of zero-order observer (ZDO), first-order observer (FDO), and second-order observer (SDO) under three different scenarios of load torque...
Keywords: Disturbance observer; frictions; high-order observer